2015
DOI: 10.1371/journal.pone.0121209
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS Expression in Colorectal Cancer

Abstract: ADAMTSs are a family of secreted proteinases that share the metalloproteinase domain with matrix metalloproteinases (MMPs). By acting on a large panel of extracellular substrates, they control several cell functions such as fusion, adhesion, proliferation and migration. Through their thrombospondin motifs they also possess anti-angiogenic properties. We investigated whether ADAMTSs participate in colorectal cancer progression and invasion. Their expression was investigated at both mRNA and protein levels. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…In this context, ADAMTS family, as a relatively new group of ECM metalloproteinases, have become one of the promising foci in the recent studies on cancer. To date, many clinical studies regarding the relationship between AD-AMTS proteases and various types of cancer have been reported (7)(8)(9)(10). However, there are limited data on the role of ADAMTSs in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, ADAMTS family, as a relatively new group of ECM metalloproteinases, have become one of the promising foci in the recent studies on cancer. To date, many clinical studies regarding the relationship between AD-AMTS proteases and various types of cancer have been reported (7)(8)(9)(10). However, there are limited data on the role of ADAMTSs in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…ADAMTS8, ADAMTS12 and AD-AMTS18) were frequently methylated and down-regulated in various carcinomas [29-31]. ADAMTS1, ADAMTS15 and ADAMTS20 are down-regulated in CRC progress [32-33]. It has also been shown that the promoters of ADAMTS1, ADAMTS5, ADAMTS9, ADAMTS12, ASDAMTS15 and ADAMTS18 are methylated in CRC, suggesting a decreased expression of the proteins in this state [29-31, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has demonstrated that ADAMTS are deregulated in human cancer and implicated in tumor progression [8,13]. Meanwhile, somatic mutations of ADAMTS genes are associated with chemotherapy sensitivity and patients' survival [20,21].…”
Section: Differentially Expressed Adamts4 Predicts a Poor Prognosis Imentioning
confidence: 99%
“…Most of ADAMTSs include the following domain structure from the N-terminus to C-terminal: 1) a signal peptide directs ADAMTS to the secretory pathway; 2) a prodomain maintains enzyme latency; 3) a zinc binding metalloproteinase domain; 4) a disintegrin-like domain; 5) a central Thrombospondin Type 1 repeat (TSR); 6) a cysteine rich domain; 7) a spacer domain; 8) variable number of TSRs [6,7]. ADAMTSs are involved in diverse functions including matrix degradation, collagen maturation, blood coagulation, organogenesis, and inflammation [8,9]. However, the functions, mechanisms of activation, and substrates of most ADAMTS members remain largely unexplored [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation